(untitled) (Bodhi Path, 2025)
The Tibetan form of Buddhism has migrated into and found its base in some places within India especially after 1959. When the migration that took place prior to 1959, there existed constant relations between the two nations (India and Tibet) which had seen the doors open for religious tolerance and intermingling. However Buddhism has always been credited to be the religion/ study that had emerged from the pious grounds of India. Though many hypotheses have been proposed on the origin of the Lepchas, it is now recognized by the government that they were and are the original inhabitants of the region now covering districts of Kalimpong, Darjeeling, and the state of Sikkim. These three regions are not new to migrants since the British era, and even prior to the British, migration had taken place in Sikkim especially from Tibet. So, one may rightly say that Tibetans were the first migrants into Kalimpong, Darjeeling and Sikkim. The areas of Kalimpong, Darjeeling and Sikkim, are also where migrants brought along with them various forms of religions and cultures that they had been practicing. Consequently, there are different religions that are prevalent in Kalimpong, Darjeeling and Sikkim namely Buddhism, Hinduism, Christianity, and Islam which are being taken up by the society that resides in these parts. The harmony in which all these religions coincide and live harmoniously sometimes adopting the others customs and traditions yet preserving their own is a uniqueness of these parts.